Myocardial Blood Flow and Flow Reserve in Patients With Acute Myocardial Infarction and Obstructive and Non-Obstructive Coronary Arteries: CZT SPECT Study - Zavadovsky, Konstantin V.; Vorobyeva, Darya A.; Mochula, Olga V.; Mochula, Andrew V.; Maltseva, Alina N.; Bayev, Andrew E.; Gulya, Marina O.; Gimelli, Alessia; Ryabov, Vyacheslav V. (Frontiers in Nuclear Medicine, 2022)
Background To assess single-photon emission computed tomography cadmium-zinc-telluride (SPECT CZT)-derived myocardial blood flow (MBF) flow reserve (MFR) and flow difference (FD) in patients with acute myocardial infarction (AMI) and to compare this data with serum cardiac troponin and cardiac magnetic resonance (CMR) findings. Methods A total of 31 patients with AMI underwent invasive coronary angiography (ICA), serial high-sensitivity serum cardiac troponin I (cTnI) measurement, and CZT SPECT with visual and quantitative (MBF, MFR, and FD) perfusion parameters, and contrast-enhanced CMR. All patients with AMI were divided into two groups: (1) with non-obstructive coronary arteries (MINOCA), n = 10; (2) with obstructive coronary artery disease (MICAD), n = 21. Results The values of SSS and SRS were significantly (p < 0.01) higher whereas global stress MBF, MFR significantly lower in patients with MICAD as compared to MINOCA – 5.0 (3.0; 5.0) vs. 9.0 (5.0; 13.0); 2.0 (1.0; 3.0) vs. 6.0 (3.0; 11.0); 2.02 (1.71; 2.37) vs. 0.86 (0.72; 1.02) ml/min/g; and 2.61 (2.23; 3.14) vs. 1.67 (1.1; 1.9), respectively. Stress MBF correlated with cTnI at 24 h and day 4: ρ = −0.39; p = 0.03 and ρ = −0.47; p = 0.007, respectively. FD correlated with cTnI at 24 h and day 4: ρ = −0.39; p = 0.03 and ρ = −0.46; p = 0.009. CMR analysis showed that infarct size, MVO and myocardial edema in patients with MICAD were significantly (< 0.05) higher as compared to MINOCA: 19.4 (10.4; 29.7) vs. 1.8 (0.0; 6.9); 0.1 (0.0; 0.7) vs. 0.0 (0.0; 0.0) and 19.5 (12.0;30.0) vs. 3.0 (0.0; 12.0), respectively. According to vessel-based analysis of CMR data, acute myocardial injury (defined as late gadolinium enhancement and myocardial edema) was observed more frequently in patients with MICAD compared to MINOCA: 34(37%) vs. 5(5%) p = 0.005, respectively. The values of regional stress MBF, MFR and FD were significantly decreased in LV territories characterized by myocardial injury compared to those without: 0.98 (0.73; 1.79) vs. 1.33 (0.94; 2.08) p < 0.01, 1.64 (1.0; 2.36) vs. 2.0 (1.53; 2.89) p < 0.01 and 0.33 (0.05; 0.57) vs. 0.56 (0.36; 1.32) p> 0.01, respectively. Conclusion In patients with AMI, SPECT CZT-derived flow measures were associated with the high-sensitivity troponin I as well as the extent of edema, microvascular obstruction, and infarct size detected by CMR. On the regional level, quantitative SPECT CZT measures were significantly lower in vessel territories characterized by myocardial injury.